Pelatihan Strategi Pembelajaran Matematika Berbasis Kemampuan Berbahasa pada Guru SD - Herli Salim; Tiurlina Tiurlina; Muhammad Hanif; Dwi Kurniasih (Jurnal Pengabdian Masyarakat PGSD, 2022)
The State Elementary School (SD) of 2 Lontar is the closest school to the UPI Marine Station, Serang Campus, which is located in Lontar, Tirtayasa District, Serang Regency. Based on interviews with classroom teachers there, most said that mathematics is the most difficult subject to teach, especially in the form of story questions. Many students are fooled and wrong in answering the question form. Especially during a pandemic like now which presents its challenges for teachers there, both in terms of material delivery, media selection, and assessment. On the other hand, mathematical literacy (numerical literacy) is a criterion that is used as an assessment in the Minimum Competency Assessment (AKM).  Referring to this, researchers will conduct community service with the target of SDN Lontar 2 teachers as an effort to improve the quality of learning, especially mathematics lessons with situational-based learning. The steps that the researcher will take are needs analysis and literature study followed by strategy formulation, implementation, direct practice, evaluation, and follow-up. The strategies compiled will be related to language skills which are a means of communication between teachers and students. The result of this empowerment is planting to identify problems and problem-solving strategies for elementary school children. The follow-up program invites teachers to continuously improve and implement situational-based learning. Teachers' understanding of the application of communicatively oriented mathematics learning methods has proven to increase after the training and the results of monitoring the implementation have also been observed